PERSEPSI GENERASI Z TERHADAP KONSEP KARIER BERKELANJUTAN DALAM ORGANISASI: STUDI GROUNDED THEORY PADA PEKERJA MUDA URBAN - Gunarda Gunarda; I Nyoman Marayasa; Reni Hindriari (LAP4B, 2026)
This research aims to build a substantive theory of how Generation Z understands, constructs, and negotiates the concept of sustainable careers in the context of modern organizations in urban areas of Indonesia. Generation Z, born between 1997 and 2012, entered the job market with a value orientation, career expectations, and relationship to work that was fundamentally different from their predecessors, but theoretical understanding of how they interpret the concept of a long-term career is still very limited and largely framed through the lens of previous generations. This study uses a constructivist Grounded Theory design following the framework of Charmaz (2014) which allows the development of theories that are directly rooted in the participants' experience data without being burdened by pre-existing theoretical propositions. Data collection was carried out through in-depth interviews and focus group discussions with twenty-two young Generation Z workers aged 22 to 27 years old who worked in various formal organizations in Jakarta, Surabaya, and Denpasar, selected through theoretical sampling which was carried out iteratively until it reached theoretical saturation. Data analysis through open coding, axial coding, and selective coding resulted in a substantive theory called